Discovery of Large Bubble-Like Caves in the Laoshan Granites and Its Significance - Zhaojun, SONG; Xiqing, LIU; Wenjia, TANG; Luo, GAO; Jianping, LI; Shaogang, LUAN (Acta geologica Sinica (Beijing), 2016)
Objective In recent years, the dispute regarding the Quatemary glacier of eastem China has become a research focus again, and one of the important focuses is the ＂glacial pothole＂. In fact, the micro-topographic genesis of the rocky surface mortar may be interpreted differently in different places, including pothole, weathering pit, sea cave and wind-eroding pot. It is very controversial to determine this ＂glacial pothole＂.